المفاوضات في عقود التجارة الدولية - حورية جزيري (My University, 2020)
NOTE SUMMARY The study aimed to clarify the general provisions for negosiation by giving a definition of negotiation and their characteristics and stages ,then contracts and preliminary agreements organizing them and their legal value, then the concept of international trade contracts , how to implement them ,methods of resolving their disputes and yhe applicable law ,so that we will then move to the strategy and legal implications . The consequences of negotiations in international trade contracts by studing negotiation strategies and skills , then the idea of re-negotiation and its terms then we touched upon the legal implications of negotiations by addressing the obligations of the negotiating parties and the nature of their responsibility , then the legal basis for this responsibility and the applicable law in trade contracts international. .............................. ملخـــــص المــــذكـــــر ة : هدفت الدراسة إلى توضيح الأحكام العامة للتفاوض من خلال إعطاء تعريف للمفاوضات وبيان خصائصها ومرحلها، ثم العقود والإتفاقيات التمهيدية المنظمة لها وقيمتها القانونية ثم مفهوم عقود التجارة الدولية وكيفية تنفيذها وطرق حل نزاعاتها والقانون المطبق عليها ، لتنتقل بعدها إلى الإستراتيجية والأثار القانونية المترتبة على المفاوضات في عقود التجارة الدولية من خلال دراسة إستراتيجيات التفاوض ومهاراته ثم فكـــــرة إعــــــادة التفاوض وشروطها ثم تطرقنا إلى الآثار القانونية المترتبة عن المفاوضات والمتمثلة في إلتزامات الأطراف المتفاوضة وطبيعة مسؤوليتهم ثم الأساس القانوني لهذه المسؤولية والقانون الواجب التطبيق على التفاوض في عقود التجارة الدولية. ....................... Résumé de la note : L’étude visait à clarifier les dispositions générales de négociation en fournissant une définition des négociations, leurs caractéristiques et phases, puis les contrats et conventions préliminaires qui les régissent et leur valeur juridique, puis la notion de contrats commerciaux internationaux et la façon dont ils sont mis en œuvre et les méthodes de règlement de leurs litiges et le droit qui leur est applicable; Ensuite, nous passons à la stratégie et aux implications juridiques des négociations dans les contrats commerciaux internationaux en examinant les stratégies et les compétences de négociation, puis l’idée de renégociation et ses conditions. Nous abordons ensuite les implications juridiques des négociations, à savoir les obligations de négociation des parties et la nature de leur responsabilité.